Novel isoforms of murine intercellular adhesion molecule-1 generated by alternative RNA splicing. - Philip D. King; Elisabeth Sandberg; Annamalai Selvakumar; Ping Fang; A L Beaudet; Bo Dupont (1995)
Abstract Intercellular adhesion molecule-1 (ICAM-1)-deficient mice, produced by homologous recombination and previously recognized to be devoid of the common form of ICAM-1, are shown to express residual amounts of ICAM-1 Ag in thymus and lung. We demonstrate that this expression of ICAM-1 is possible because the mutated exon 5 in these animals has been skipped by alternative splicing of RNA. Three different alternative isoforms of ICAM-1 are expressed in mutant mice. Moreover, two of these isoforms are expressed in wild-type mice together with two additional alternative isoforms that cannot be produced in mutant mice. All alternatively spliced isoforms of ICAM-1 detected are missing complete extracellular Ig domains. In both mutant and wild-type mice, expression of alternatively spliced isoforms is up-regulated following stimulation of animals with LPS. Furthermore, all alternative isoforms of ICAM-1, except one, retain the ability to bind to the well-recognized ICAM-1 counter-receptor LFA-1. These findings, along with the restricted tissue distribution in mutant mice, indicate that alternative isoforms of ICAM-1 are significant physiologic adhesion structures which could play a distinct role in the functioning of the immune system of intact animals.